A SUCCESSFUL EDUCATIONAL INTERVENTION LINKING DEMENTIA PATIENTS AND FAMILIES WITH COMMUNITY RESOURCES. (20th December 2022) - Barnes, Stacy; Duthie, Edmund; Denson, Kathryn; McAlister, Jennifer; Betley, Wendy; Szymkowski, Amanda; Malone, Michael; Simpson, Deborah
Abstract: Unpaid caregivers provided approximately 83% of the care for the 6.2 million Americans aged 65+ who were living with Alzheimer's dementia in 2021. Physicians and other health professionals are not well informed about dementia-related community resources and rarely refer patients/families despite strong evidence which supports incorporating community services as part of an ongoing treatment plan. To bridge this gap, partnership with community agencies is essential. The Alzheimer's Association's "Direct Connect" referral program is provider-initiated and connects patients/families with disease information, care consultations, support groups, a 24/7 Helpline, and other resources. As part of the Wisconsin Geriatric Workforce Enhancement Program award from HRSA (U1QHP28712) 1, 023 health professionals working in Wisconsin hospitals and primary care clinics were trained to use Direct Connect. Our educational intervention re-framed dementia from a hopeless disease to a chronic condition requiring supportive services as a necessary component of the disease management plan. Results of a paired-samples t-test (n=675) indicated our educational intervention had a significant impact on trainees' self-reported pre/post-test knowledge in both hospitals [t(444) = -34.67, p < 0.001, d = 1.64] and primary care [t(229) = -24.63, p < 0.001, d = 1.62]. By the end of the 5-year project period, Direct Connect referrals totaled 1, 352 and the program grew from less than 50 referrals to 290 annually. While these results are promising, Direct Connect remains underutilized and initiatives to further increase referrals from providers must be expanded.